Economic valuation of selected coastal ecosystems based on key provisioning and regulation services of Jaguaruna (Brazil) - Sfreddo, Giuliana Andréia; Chica Ruiz, Juan Adolfo; Silva da Silva, Tatiana; Barboza, Eduardo Guimarães (Desenvolvimento e Meio Ambiente, 2023)
The search for sustainability can be understood as a trajectory towards the maintenance of ecosystem services, which includes ways of minimizing the risk of losing them due to some imminent coastal hazard. Thus, this study aimed to evaluate the state of key-ecosystem services of provisioning and regulation in the southern coast of the state of Santa Catarina in the face of coastal stressors. For the development of the research, eight types of ecosystems were identified and mapped, according to a key ecosystem service offered by each of them, and the four largest in area were selected to apply the environmental valuation methodologies. The methodologies used were the Avoided Costs Method (ACM) and the Replacement Cost Method (RCM). The ACM calculates the economic value of the benefits that an ecosystem provides that would not be available if it did not exist. In turn, the RCM is based on the replacement cost of a damaged asset. Valuation results for Agriculture and Cattle farming; Continental waters and Marine environment; and Afforestation were respectively 1.74; 2.86; 2.89 million of dollars per year, while results for Dunes, Beaches and Restingas were in the range of USD 3,120–6,240 ha-1 yr-1. These values should be understood as approximations of the true economic dimension of the damages caused by the use of ecosystems, since they correspond to how much the environment is capable of monetarily returning to individuals. Furthermore, these values cannot be used to calculate fines in case of environmental degradation.